2012
DOI: 10.5483/bmbrep.2012.45.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Sodium selenite-induced activation of DAPK promotes autophagy in human leukemia HL60 cells

Abstract: Autophagy has been suggested as a possible mechanism for non-apoptotic death despite evidence from many species that autophagy represents a survival strategy of cells under stress. From our previous findings that supranutritional doses of sodium selenite induced apoptosis in human leukemia cells, now we show autophagic cell death occurred after selenite exposure in HL60, suggested an alternative mechanism for the potential therapeutic properties of selenite. Additionally, Death-associated Protein Kinase (DAPK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Jiang et al . documented that sodium selenite‐induced activation of DAPK promotes autophagy. In our early study, we also found a positive role of DAPK in autophagy induction, as SB203580, a pyridinyl imidazole, induced autophagy via activating DAPK to maintain the survival of HCC cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al . documented that sodium selenite‐induced activation of DAPK promotes autophagy. In our early study, we also found a positive role of DAPK in autophagy induction, as SB203580, a pyridinyl imidazole, induced autophagy via activating DAPK to maintain the survival of HCC cells .…”
Section: Discussionmentioning
confidence: 99%
“…Kiyono et al [24] reported that transforming growth factor-beta activated autophagy to tender its growth inhibitory effect on tumour cells. Jiang et al [25] documented that sodium selenite-induced activation of DAPK promotes autophagy. In our early study, we also found a positive role of DAPK in autophagy induction, as SB203580, a pyridinyl imidazole, induced autophagy via activating DAPK to maintain the survival of HCC cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…1 Recently, autophagy has been recognized as a cell death mechanism that takes place in various types of cancer cells in response to anticancer therapies. 2 …”
mentioning
confidence: 99%
“…9 In addition, reports using other cell lines have shown that selenite promotes both autophagy and apoptosis. 10, 11, 12, 13 On the basis of these previous studies, elucidating the relationship between autophagy and apoptosis in cancer cells after selenite exposure is necessary.…”
mentioning
confidence: 99%